High Speed Stability of a Railway Vehicle Equipped with Independently Rotating Wheels (preprint) - Kyryl’chuk, Oleg A.; Kalivoda, Jan; Neduzha, Larysa O. (Ústav Teoretické a Aplikované Mechaniky, Prosecká, Czech Republic, 2018)
EN: The paper is devoted to the study of lateral oscillation and the assessment of the motion stability of a four axle railway vehicle equipped with wheelsets with independently rotating wheels. First, a linear four degrees of freedom mathematical model of the unconstrained wheelset in a straight track has been built. The wheelset model was consequently utilized in a model of the whole vehicle representing typical railway passenger car. The model has 25 degrees of freedom and it is described by a system of 50 first order homogeneous differential equations. Linear algebra methods were used to assess the stability. The influence of a running velocity, the torsional stiffness of wheelsets and the viscosity of coupling element between wheels was studied. Results of this study shows that wheelsets with independently rotating wheels and viscous coupling element enable stable behaviour of a vehicle at speeds exceeding 500 km/h. Prospectively, this type of wheelset is applicable to high-speed railway vehicles, because it offers either further increase of running speeds or simplification of running gear while preserving high speed stability.
L. Neduzha: ORCID 0000-0002-7038-3006, O. Kyryl’chuk: ORCID 0000-0002-0565-1692
Keywords: railway wheelset; independently rotating wheels; lateral dynamics; stability; КТБМ; КВВГ